2014
DOI: 10.1161/atvbaha.114.303393
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase 9 Represses Cholesterol Efflux and Alternatively Activated Macrophages in Atherosclerosis Development

Abstract: Objective Recent genome-wide association studies revealed that a genetic variant in the loci corresponding to histone deacetylase 9 (HDAC9) is associated with large vessel stroke. HDAC9 expression was upregulated in human atherosclerotic plaques in different arteries. The molecular mechanisms how HDAC9 might increase atherosclerosis is not clear. Approach and Results In this study, we show that systemic and bone marrow cell deletion of HDAC9 decreased atherosclerosis in LDLr−/− mice with minimal effect on pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
139
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(142 citation statements)
references
References 38 publications
3
139
0
Order By: Relevance
“…A recent study found that targeted depletion of HDAC9 in bone marrow cells attenuates atherogenesis in LDLr −/− mice. 19 HDAC9 was further shown to repress cholesterol efflux in macrophages. However, whether the changes in macrophages give rise to atherosclerotic lesion formation remains speculative.…”
Section: January 2015mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study found that targeted depletion of HDAC9 in bone marrow cells attenuates atherogenesis in LDLr −/− mice. 19 HDAC9 was further shown to repress cholesterol efflux in macrophages. However, whether the changes in macrophages give rise to atherosclerotic lesion formation remains speculative.…”
Section: January 2015mentioning
confidence: 99%
“…However, we cannot exclude skewing of macrophage polarization from M1 to M2 phenotype as previously reported. 19 The precise mechanisms by which increased HDAC9 expression promotes atherogenesis and vascular risk remain to be determined. A recent study found that targeted depletion of HDAC9 in bone marrow cells attenuates atherogenesis in LDLr −/− mice.…”
Section: January 2015mentioning
confidence: 99%
“…[142][143][144][145][146][147] Identification and characterization of common epigenetic outcomes linked to disease manifestations and their interaction with nutrient status may allow the development of specific treatment and intervention measures. [148][149][150][151] Interestingly, the effect of limited or oversaturated nutrient bioavailability on epigenetic states is complex and not necessarily direct. For example, deficiency of methyl donors results in hypermethylation at some loci and hypomethylation at others.…”
Section: Role Of Nutrition In Epigenetic Perturbationmentioning
confidence: 99%
“…26 Moreover, overexpression of macrophage HDAC9 was reported to be atherogenic via inhibition of cholesterol efflux and the generation of alternatively activated macrophages. 27 However, the role of HDAC9 in atherosclerosis has not yet been fully elucidated.…”
Section: Effects Of Mir-182 On Hdac9mentioning
confidence: 99%